From molecular to continuum modelling of bistable liquid crystal devices. Issue 14 (8th December 2017) - Robinson, Martin; Luo, Chong; Farrell, Patrick E.; Erban, Radek; Majumdar, Apala
ABSTRACT: We study nematic equilibria on a square with tangent Dirichlet conditions on the edges, in three different modelling frameworks: (i) the off-lattice Hard Gaussian Overlap and Gay–Berne models; (ii) the lattice-based Lebwohl–Lasher model; and the (iii) two-dimensional Landau-de Gennes model. We compare the modelling predictions, identify regimes of agreement and in the Landau-de Gennes case, find up to 21 different equilibria. Of these, two are physically stable. GRAPHICAL ABSTRACT: